Análisis de los estilos de liderazgo de los colaboradores de Scotiabank de la ciudad de Iquitos, año 2020 - Guevara Garcia, Cissella Itzell (2021)
The objective of the research was to describe the influence of leadership styles on Scotiabank employees in the city of Iquitos, year 2020. The methodology was quantitative, with a non-experimental, cross-sectional descriptive research design. The population and sample consisted of 35 employees of Scotiabank from the City of Iquitos, period 2020, being a non-probabilistic sampling. The survey technique was applied, a 21-question questionnaire was used as an instrument for collecting the information for the variable under study, structured leadership style in the dimensions: transformational leadership and transactional leadership using a Likert-type scale. The result of the descriptive analysis of the transformational leadership dimension is characterized by an influence by an idealized, inspirational and motivational change, being 71% high level transformational leadership, 29% moderate level and 0% low level. In the transactional leadership dimension, it is characterized by an influence motivated by exchange or reward between the leader and followers, being a transactional leadership of a high level of 40%, 57% of a moderate level and only 3% of a low level. We conclude that the diagnosis percentage is that 63% are influenced by a transformational leadership style based on idealized, inspirational and motivational influence and 37% by a transactional leadership style based on an influence of exchange and reward.